Cardiac Remote Ischemic Preconditioning Prior to Elective Vascular Surgery (CRIPES): A Prospective, Randomized, Sham‐Controlled Phase II Clinical Trial. Issue 10 (29th September 2016) - Garcia, Santiago; Rector, Thomas S.; Zakharova, Marina; Herrmann, Rebekah R.; Adabag, Selcuk; Bertog, Stefan; Sandoval, Yader; Santilli, Steve; Brilakis, Emmanouil S.; McFalls, Edward O.
Abstract : Background: Remote ischemic preconditioning (RIPC) has been shown to reduce infarct size in animal models. We hypothesized that RIPC before an elective vascular operation would reduce the incidence and amount of a postoperative rise of the cardiac troponin level. Methods and Results: Cardiac Remote Ischemic Preconditioning Prior to Elective Vascular Surgery (CRIPES) was a prospective, randomized, sham‐controlled phase 2 trial using RIPC before elective vascular procedures. The RIPC protocol consisted of 3 cycles of 5‐minute forearm ischemia followed by 5 minutes of reperfusion. The primary endpoint was the proportion of subjects with a detectable increase in cardiac troponin I (cTnI) and the distribution of such increases. From June 2011 to September 2015, 201 male patients (69±7, years) were randomized to either RIPC (n=100) or a sham procedure (n=101). Indications for vascular surgery included an expanding abdominal aortic aneurysm (n=115), occlusive peripheral arterial disease of the lower extremities (n=37), or internal carotid artery stenosis (n=49). Of the 201 patients, 47 (23.5%) had an increase in cTnI above the upper reference limit within 72 hours of the vascular operation, with no statistically significant difference between those patients assigned to RIPC (n=22; 22.2%) versus sham procedure (n=25; 24.7%; P =0.67). Among the cohort with increased cTnI, the median peak values (interquartile range) in the RIPC and control group were 0.048 (0.004–0.174) and 0.017 (0.003–0.105), respectively ( P =0.54). Conclusions: In this randomized, controlled trial of men with increased perioperative cardiac risks, elevation in cardiac troponins was common following vascular surgery, but was not reduced by a strategy of RIPC. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01558596.